OPERATIONAL STRATEGIES TO IMPROVE COAL HAULING PRODUCTIVITY AT PT BORNEO - Joko Pamungkas, Galuh
PT BORNEO is among the top five mining companies in terms of coal production in 2022, aiming to produce 36 million tons of coal. As production quotas have significantly increased, various aspects such as equipment scale, haul distance, equipment density, and safety risks have also increased. Consequently, several operational performances have suffered a decline, one of which is the productivity of hauling ROM to PORT (RTP), achieving only approximately 86% of the target. To overcome the problem, the issues were analyzed using cause mapping, the 5 Whys technique, interviews and statistical tools to pinpoint the potential root causes. Potential root causes were examined further using appropriate statistical and simulation tools to identify the actual underlying causes. Based on the analysis, there are two major root causes that have the highest contribution to the RTP productivity, unbalanced trucks movement and PORT capacity which less than Hauling capacity. Each of these root causes further broke down into six operational variables representing the root causes. Simulation showed that there are three primary factors contribute to the low productivity of RTP: loading time, random stoppages during shifts, and the composition of loaded and empty change shifts.